The Expression and Localization of Crb3 in Developmental Stages of the Mice Embryos and in Different Organs of 1‐week‐old Female Mice. Issue 5 (12th August 2014) - Yin, Y; Sheng, J; Hu, R; Yang, Y; Qing, S
Contents Crumbs homolog 3 (Crb3) is a member of the Crumbs family of proteins. This protein may play a role in epithelial cell polarity and is associated with tight junctions at the apical surface of epithelial cells. Alternative transcriptional splice variants that encode different Crb3 isoforms have been characterized. The expression of Crb3 mRNA and protein was observed in the pre‐implantation mouse embryos and different organs of 1‐week‐old mouse, and Crb3 expression was primarily observed in the cytoplasm. Crb3 was expressed in a unique temporal pattern in pre‐implantation embryos. The main characteristic of Crb3 expression was that the positive signals were stronger in the mature oocytes and zygotes than in the 2‐cell, 4‐cell, and 8‐cell stages and the morula, but a similar level of high expression was observed in blastocysts. Therefore, the Crb3 expression signal during the course of development process grew gradually stronger from the 2‐cell stage to blastocyst. In addition, Crb3 protein was widely distributed in each stage of the post‐implantation embryos. Crb3 expression was observed in the inner cell mass, trophoblast cells and endoderm of E4.5d embryos; in the chorion, amnion, trophoblast cells, yolk sac endoderm and embryo ectoderm of E7.5d embryos; in the amnion and limb bud of E8.0d embryos; and in the semicircular canal epithelium, retina, lens vesicle and liver tissue of E13.5d embryos. Crb3 was expressed at different levels in different organs of 1‐week‐old mouse with the strengths in the following order: kidney > small intestine > stomach > uterus > liver > skeletal muscle > cerebellum > brain. The presence of Crb3 in many organs and the regularity of Crb3 distribution in the process of mouse embryonic development indicate that Crb3 protein plays an important role in establishing and maintaining the polarity of mouse embryos.